Анализ инцидентов на нефтеперерабатывающем предприятии - Bulavka Юлия; Smilovenko Ольга; Stashevich Е. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2012)
The systematic data on the frequency and causes of the incidence in one of the oil refineries in the Republic of Belarus for the period from 1998 to 2011 are presented in this article. The ranking of the number of incidents at departments, groups and types of effects (failures of degree I, II, damage of degree I, II, violation) is given. The dynamics of the time factor (year, month, day of week), the number of incidents at hazardous production facilities, plant downtime and the amount of material damage to the refinery has been determined. The obtained results of the analysis of incidents can become the basis for their prognosis and the guide managed to eliminate the causes, to reduction of occupational risks and to ensure the highest efficiency of preventive measures at the lowest cost.